Herzberg's maintenance factor satisfaction/dissatisfaction of library student assistants in U.P. Diliman Libraries - Garcia, Justina D. (2004)
This study is focused on the library student assistants at UP Diliman libraries using Herzberg's maintenance factor of satisfaction/dissatisfaction. A total of 62 library student assistants employed during the second semester of academic year 2003-2004 various libraries of the university. A survey determined the following: 1) profile of the respondents with regards to sex/gender, degree major (BLIS/non BLIS), year level in college, with financial assistance, library/unit assigned and length of service; 2) satisfaction/dissatisfaction of library student assistants based on Herzberg's maintenance factors satisfaction/dissatisfaction; 3) male and female library student assistants satisfaction/dissatisfaction and the significant differences between male and female satisfaction/dissatisfaction for each maintenance factor; 4) BLIS and non BLIS satisfaction/dissatisfaction and the significant differences between BLIS and non BLIS satisfaction/dissatisfaction for each maintenance factor; 5) with financial assistance and without financial assistance satisfaction/dissatisfaction and the significant differences between the two respondents satisfaction/dissatisfaction for each maintenance factor. Descriptive method of research was used to determine the objectives of the study.